Science and the Written Word : Science, Technology, and Society. - Massa, Lou (Oxford University Press, USA, 2011)
In order to meet the growing scientific requirements of an increasingly complex society, it is essential for us to have an appreciation of the power and breadth of science. Science and the Written Word is a collection of interviews featuring some of the world's greatest scientists and Nobel Prize winners. The interviews examine topics related to the nature of science and technology, making them more accessible to the general reader, and emphasize the relationship of various scientific disciplines to one another. Through this book, readers learn from the "inside" how science is done.